CCNA 200-301 Official Cert Guide Library - Odom, Wendell (Cisco Press, 2019)
Cisco Press has the only study guides approved by Cisco for the new CCNA certification. The new edition of the best-selling two-book value-priced CCNA 200-301 Official Cert Guide Library includes updated content, new online practice exercises, more than 600 practice exam questions, and more than 2 hours of video training-PLUS the CCNA Network Simulator Lite Editions with 34 free Network Simulator labs. CCNA 200-301 Official Cert Guide Library is a comprehensive review and practice package for the latest CCNA exam and is the only self-study resource approved by Cisco. The two books contained in this package, CCNA 200-301 Official Cert Guide, Volume 1 and CCNA 200-301 Official Cert Guide, Volume 2, present complete reviews and a more challenging and realistic preparation experience. The books have been fully updated to refresh the content for the latest CCNA exam topics and to enhance certain key topics that are critical for exam success. Best-selling author Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete study package includes · A test-preparation routine proven to help you pass the exams · Do I Know This Already? quizzes, which enable you to decide how much time you need to spend on each section · Chapter-ending Key Topic tables, which help you drill on key concepts you must know thoroughly · The powerful Pearson Test Prep Practice Test software, complete with hundreds of well-reviewed, exam-realistic questions, customization options, and detailed performance reports · A free copy of the CCNA 200-301 Network Simulator Lite software, complete with meaningful lab exercises that help you hone your hands-on skills with the command-line interface for routers and switches · Links to a series of hands-on config labs developed by the author · Online interactive practice exercises that help you enhance your knowledge · More than 2 hours of video mentoring from the author · An online interactive Flash Cards application to help you drill on Key Terms by chapter · A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies · Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, study plans, assessment features, hands-on labs, and challenging review questions and exercises, this officia ...